2014
DOI: 10.1080/07038992.2014.979487
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Scattering Behaviour and Assessing Potential for Classification of Arctic Shore and Near-Shore Land Covers with Fine Quad-Pol RADARSAT-2 Data

Abstract: Freeman-Durden and Cloude-Pottier decompositions were applied to polarimetric RADARSAT-2 data to characterize the scattering behaviour of shore and near-shore land cover types for two study areas in the Beaufort Sea, Canada: Richards Island and Tuktoyaktuk Harbour. The impact of incidence angle was evaluated through comparison of Single Look Complex Fine Quad-Pol images acquired at three angles: shallow (45.3 • -49.5 • ), medium (39.3 • -41.6 • ), and steep (20.9 • -24.2 • ), and the potential for accurate cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…The authors demonstrated potential for classifier transferability by applying both models trained on data from the Richards Island site to the Ivvavik site, achieving overall accuracies of 71% and 78% for the pixel and object-based approaches, respectively. Notably, these results were attained with RADARSAT-2 images that were acquired on different dates, and at different incidence angles (~34°-36° (FQ15) over Richards Island, and ~48°-49° (FQ30) over Ivvavik), the latter of which has been shown to affect the backscattering behaviour of some shoreline classes [11,12].…”
Section: Potential For Shoreline Sensitivity Mapping Using Earth Obsementioning
confidence: 99%
See 3 more Smart Citations
“…The authors demonstrated potential for classifier transferability by applying both models trained on data from the Richards Island site to the Ivvavik site, achieving overall accuracies of 71% and 78% for the pixel and object-based approaches, respectively. Notably, these results were attained with RADARSAT-2 images that were acquired on different dates, and at different incidence angles (~34°-36° (FQ15) over Richards Island, and ~48°-49° (FQ30) over Ivvavik), the latter of which has been shown to affect the backscattering behaviour of some shoreline classes [11,12].…”
Section: Potential For Shoreline Sensitivity Mapping Using Earth Obsementioning
confidence: 99%
“…In a follow-up paper Banks et al [12] assessed the potential to classify shore and near-shore land cover types using unsupervised polarimetric SAR classifiers, including: Wishart-entropy/alpha, Wishart-entropy/anisotropy/alpha, and Freeman-Wishart [18,19]. The authors applied each classifier to the same six images used by Banks et al [11], and found that they could detect more land covers using the shallow and medium incidence angle images.…”
Section: Potential For Shoreline Sensitivity Mapping Using Earth Obsementioning
confidence: 99%
See 2 more Smart Citations
“…Former studies have thrown light on the potentials of the features extracted from optical and SAR data source and abilities of discrimination of tidal water, sediment and other biotic community. (Baghdadi et al, 2013;Banks et al, 2014a;Banks et al, 2014b;Brockmann and Stelzer, 2008;Gade et al, 2008;Koch et al, 2012;Ullmann et al, 2014). But there are rarely studies focus on subdividing sediment types which can promote economic development and environmental protection.…”
Section: Introductionmentioning
confidence: 99%